ITiCSE 2021 recap - Schulte, Carsten; A. Becker, Brett (ACM SIGCSE Bull.)

Joining of Sheet Metal and Thermoplastic Composites Using Injection Riveting - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes

Fügen von thermoplastischen Composites mit Metallteilen durch Spritznieten - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes (Joining Plastics)

Influence of Plasmon Resonances and Symmetry Effects on Second Harmonic Generation in WS2–Plasmonic Hybrid Metasurfaces - Spreyer, Florian; Ruppert, Claudia; Georgi, Philip; Zentgraf, Thomas (ACS Nano)
The nonlinear process of second harmonic generation (SHG) in monolayer (1L) transition metal dichalcogenides (TMD), like WS2, strongly depends on the polarization state of the excitation light. By combination of plasmonic nanostructures with 1L-WS2 by transferring it onto a plasmonic nanoantenna array, a hybrid metasurface is realized impacting the polarization dependency of its SHG. Here, we investigate how plasmonic dipole resonances affect the process of SHG in plasmonic–TMD hybrid metasurfaces by nonlinear spectroscopy. We show that the polarization dependency is affected by the lattice structure of plasmonic nanoantenna arrays as well as by the relative orientation between the 1L-WS2 and the individual plasmonic nanoantennas. In addition, such hybrid metasurfaces show SHG in polarization states, where SHG is usually forbidden for either 1L-WS2 or plasmonic nanoantennas. By comparing the SHG in these channels with the SHG generated by the hybrid metasurface components, we detect an enhancement of the SHG signal by a factor of more than 40. Meanwhile, an attenuation of the SHG signal in usually allowed polarization states is observed. Our study provides valuable insight into hybrid systems where symmetries strongly affect the SHG and enable tailored SHG in 1L-WS2 for future applications.

Learning From Revisions: Quality Assessment of Claims in Argumentation at Scale - Skitalinskaya, Gabriella; Klaff, Jonas; Wachsmuth, Henning (Proceedings of the 16th Conference of the European Chapter of the Association for Computational Linguistics)

Learning Flow Scheduling - Hasnain, Asif; Karl, Holger (2021 IEEE 18th Annual Consumer Communications & Networking Conference (CCNC))
Datacenter applications have different resource requirements from network and developing flow scheduling heuristics for every workload is practically infeasible. In this paper, we show that deep reinforcement learning (RL) can be used to efficiently learn flow scheduling policies for different workloads without manual feature engineering. Specifically, we present LFS, which learns to optimize a high-level performance objective, e.g., maximize the number of flow admissions while meeting the deadlines. The LFS scheduler is trained through deep RL to learn a scheduling policy on continuous online flow arrivals. The evaluation results show that the trained LFS scheduler admits 1.05x more flows than the greedy flow scheduling heuristics under varying network load.
Keywords: Flow scheduling; Deadlines; Reinforcement learning

Extending Business Model Development Tools with Consolidated Expert Knowledge - Gottschalk, Sebastian; Kirchhoff, Jonas; Engels, Gregor (Business Modeling and Software Design)

Dietary Glycaemic Index Labelling: A Global Perspective. - Barclay, AW; LSA, Augustin; Brighenti, F; Delport, E; Henry, CJ; Sievenpiper, JL; Usic, K; Yuexin, Y; Zurbau, A; TMS, Wolever; Astrup, A; Bulló, M; et al. (Nutrients)

Die Gestaltung des Übergangs zur Weiterführenden Schule – Welche Maßnahmen wurden und werden an Grundschulen in NRW praktiziert? - van Ophuysen, Stefanie; Schürer, Sina; Bloh, Bea (Zeitschrift für Grundschulforschung)
Zusammenfassung Studien zum Übergang von der Grund- in die weiterführende Schule gibt es zu zahlreichen Themen. Wie Grundschulen den Übergang zur weiterführenden Schule gestalten, wurde bislang jedoch kaum erforscht. Auf Basis des Forschungsstands werden relevante Maßnahmen identifiziert. In einer online-Befragung an 106 Grundschulen in Nordrhein-Westfalen wurde erfasst, inwiefern diese Maßnahmen tatsächlich umgesetzt werden und als wie relevant bzw. schwierig ihre Umsetzung erachtet wird. Die Ergebnisse werden verglichen mit Daten einer Studie, die 2002 an 71 Grundschulen durchgeführt wurde. Es zeigt sich eine hohe Stabilität der Gestaltung in den letzten 15 Jahren. Maßnahmen, die auf stufenübergreifender Kooperation basieren, werden heute zwar häufiger praktiziert, stehen aber weiterhin am Ende der Rangreihe.

Die Perspektive von Referendar*innen auf Forschendes Lernen - Homt, Martina; Bloh, Bea